Successful minimally invasive management using transcatheter arterial embolization in a hemodynamically stable elderly patient with mesenteric vascular injury in a hybrid emergency room system in Korea: a case report - Ahn, So Ra; Lee, Joo Hyun; Seo, Sang Hyun; Park, Chan Yong (Daehan oe'sang haghoeji, 2023)
Mesenteric injury occurs rarely in cases associated with blunt abdominal trauma. Despite its low incidence, mesenteric injury can lead to fatal outcomes such as hypovolemic shock due to hemoperitoneum or sepsis due to intestinal ischemia, or perforation-related peritonitis. For mesenteric injuries, especially those involving massive bleeding, intestinal ischemia, and perforation, the standard treatment is surgery. However, in the case of operative management, it should be borne in mind that there is a possibility of complications and mortality during and after surgery. The usefulness of transcatheter arterial embolization (TAE) is well known in solid organs but is controversial for mesenteric injury. We present a 75-year-old man with mesenteric injury due to blunt abdominal trauma. Initial abdominal computed tomography showed no hemoperitoneum, but a mesenteric contusion and pseudoaneurysm with a diameter of 17 mm were observed near the origin of the superior mesenteric artery. Since there were no findings requiring emergency surgery such as free air or intestinal ischemia, it was decided to perform nonoperative management with TAE using microcoils in hybrid emergency room system. TAE was performed successfully, and there were no complications such as bleeding, bowel ischemia, or delayed bowel perforation. He was discharged on the 23rd day after admission with percutaneous catheter drainage for drainage of mesenteric hematoma. The authors believe that treatment with TAE for highly selected elderly patients with mesenteric injuries has the positive aspect of minimally invasive management, considering the burden of general anesthesia and the various avoidable intraoperative and postoperative complications.